A ‘NEW NORMAL’ OF CODE-SWITCHING: COVID-19, THE INDONESIAN MEDIA AND LANGUAGE CHANGE - Foster, Stuart Mannix; Welsh, Alistair (Indonesian Journal of Applied Linguistics, 2021)
The COVID-19 pandemic has changed behavioural norms and how people conceptualise everyday life. It has led to prolific use of specific terminology that is new or was previously outside the lexical boundaries of common use. Terms like ‘social distancing’, ‘lockdown’ and ‘new normal' were previously jargon limited to specialist fields. The COVID-19 pandemic which spread globally in 2020 has led to great social change and an associated lexical influence. To study this phenomenon, we examine the lexical effects of COVID-19 on the Indonesian language, through analysis of two well-known Indonesian national newspapers – Kompas and Suara Pembaruan, for the month of May 2020. This was at a time of growing awareness of COVID-19 in Indonesia, that included a partial lockdown in Jakarta. As such, there was a great deal of attention to COVID-19 in the mass media. To study this, we apply quantitative content analysis to the sample data to identify the range and frequency of words borrowed from English. We examine this use of code-switching to also undertake qualitative analysis, exploring the various socio-linguistic dimensions of those borrowed terms. Some usage was found to address lexical gaps in Indonesian language, where other usage appeared more for stylistic, emphatic purposes, drawing on the semiotic power of English in the Indonesian context. Code-switching reiteration was particularly prominent in the sample data. We argue that through code-switching reiteration, the print media can introduce new foreign vocabulary to Indonesian readers, which subsequently generates opportunities for language change. COVID-19 has expedited this process, meaning that there has been an increased likelihood of Indonesian language change during 2020.